2024
DOI: 10.1093/jas/skae001
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of guanidinoacetic acid in a low metabolizable energy diet improves broilers growth performance by elevating energy utilization efficiency through modulation serum metabolite profile

Sumei Cao,
Weizhen He,
Guanghai Qi
et al.

Abstract: This study was aimed to explore the elevating energy utilization efficiency mechanism for the potentially ameliorative effect of guanidinoacetic acid (GAA) addition on growth performance of broilers fed a low metabolizable energy (LME) diet. A total of 576 day-old broilers were randomly allocated to one of the 6 treatments: a basal diet (normal ME, positive control, PC), or an LME diet (50 kcal/kg reduction in ME, negative control, NC) supplemented with 0.02, 0.04, 0.06 and 0.08 % GAA from 1 to 42 d of age, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…However, no interaction was observed between sex and GAA supplementation in growth performance and carcass traits. Our results are consistent with those of Cao et al [27] who reported that dietary supplementation with GAA did not affect BW, BWG, or carcass traits and enhanced FCR, particularly in low-metabolizable-energy diets. Additionally, Mousavi et al [28] observed that supplementing GAA improved FCR without noticeably affecting BW in broiler-fed diets with varying energy content.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, no interaction was observed between sex and GAA supplementation in growth performance and carcass traits. Our results are consistent with those of Cao et al [27] who reported that dietary supplementation with GAA did not affect BW, BWG, or carcass traits and enhanced FCR, particularly in low-metabolizable-energy diets. Additionally, Mousavi et al [28] observed that supplementing GAA improved FCR without noticeably affecting BW in broiler-fed diets with varying energy content.…”
Section: Discussionsupporting
confidence: 93%
“…This observation correlated with enhanced growth performance noticed in this experiment. These findings align with studies by Cao et al [27], who found no alterations in hepatic enzymes in the birds fed diets with GAA ranging from 0.02% to 0.08% compared to those that were fed normal and low-metabolizable-energy diets. Similarly, Khalil et al [43] and Amiri et al [47] reported meaningless alterations in thyroid hormone activities with GAA inclusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation